Limnomermis subtropicalis n. sp. (Nematoda:Mermithidae) a Parasite of Larvae of Simulium orbitale Lutz (Diptera:Simuliidae) in Argentina - Villalobos, Cristina de (1997)
Limnomermis subtropicalis n. sp. (Nematoda: Mermithidae) a parasite of Simulium orbitale Lutz (Diptera: Simuliidae) found in Argentina is described and illustrated. This species is characterized by having medium sized amphids, pocket-shaped, medium sized vagina, sculptured spicule, and by having 9 preanal, 7 postanal papillae in the ventral row, and 12 papillae in the lateral rows.